Tata Kelola Kebijakan Sistem Kerja Pegawai di Lingkungan Kementerian Hukum dan HAM dalam Kerangka Penyederhanaan Birokrasi - Nizar Apriansyah; Maharini Maharini (Jurnal Ilmiah Kebijakan Hukum, 2024)
The bureaucracy in Indonesia still faces serious challenges, such as inefficiency, corruption, collusion, nepotism, and public dissatisfaction with government services. To establish a clean, accountable, and professional government, the Indonesian government has undertaken various bureaucratic simplification efforts in line with the mandate of Presidential Regulation No. 18 of 2020. These measures include transitioning administrative officials to functional roles, restructuring work systems to enhance performance, and promoting a more collaborative and dynamic digital governance model. This study employs a qualitative approach with descriptive analysis to evaluate the implementation of bureaucratic simplification, focusing on the work system policy for employees within the Ministry of Law and Human Rights. Data was collected through interviews with officials from various work units and literature reviews from scientific sources and relevant regulations. The discussion centers on the application of organizational restructuring, position equalization, and work system adjustments within the Ministry. Although these efforts have been successful at the central level, challenges remain at the regional level. The results indicate that while significant progress has been made, further evaluation and adjustments are necessary, particularly regarding employee work system policies at the Regional Office and Technical Implementation Unit levels. Full support from all employees and stakeholders is essential to achieve a more efficient and responsive bureaucracy.